Russian consensus on the use of incobotulinumtoxinA in children with cerebral palsy for the treatment of spasticity and sialorrhea - A. L. Kurenkov; L. M. Kuzenkova; B. I. Bursagova; V. V. Chernikov; O. V. Agranovich; L. G. Khachatryan; V. M. Kenis; V. A. Zherebtsova; M. N. Sarzhina; N. D. Odinaeva; A. R. Artemenko; G. A. Popova; et al. (Неврология, нейропсихиатрия, психосоматика, 2022)
Botulinum therapy for cerebral palsy (CP) is considered not only as one of the effective approaches for the treatment of increased muscle tone and spasticity, but also as a method of excessive salivation correction. The article presents an overview of the results of Russian and foreign studies on the efficacy and safety of incobotulinumtoxinA for the treatment of spasticity of the lower and upper limbs, as well as sialorrhea in patients with CP. The article also provides a consensus opinion of Russian specialists working with patients with CP and using Xeomin (incobotulinumtoxinA) in their practice for the treatment of spasticity and sialorrhea. This consensus was based on the results of a Russian retrospective multicenter study on the use of incobotulinumtoxinA for the treatment of spasticity and sialorrhea in CP, data from recently published international clinical trials, and our own clinical experience. We present detailed practical recommendations on the calculation of the total dose of incobotulinumtoxinA per procedure for the treatment of spasticity in CP, on the calculation of incobotulinumtoxinA dose for the most common target muscles (lower and upper limbs) for spasticity treatment in CP, on incobotulinumtoxinA dilution and dose calculation for sialorrhea treatment in children, on incobotulinumtoxinA dilution and dose calculation for simultaneous treatment of spasticity and sialorrhea in CP. We justify incobotulinumtoxinA use, when simultaneous treatment of spasticity and sialorrhea is necessary, which allows reducing the intervals between repeated injection cycles. IncobotulinumtoxinA use in children with CP demonstrates a favorable safety profile, including long-term use.